Pengaruh Persepsi Harga, Online Customer Review Dan Promosi Terhadap Keputusan Pembelian Produk Heylook Official Shop Pada Market Place Shopee - Pingkan Atmarti Arumingtyas; Yugi Setyarko; Ravindra Safitra Hidayat (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
The development of information technology in a digital-based economy supports business actors in aspects of marketing, procurement, distribution, and consumer service. This research aims to determine the influence of price perceptions, online customer reviews, and promotions on purchasing decisions for Heylook Official Shop products on the Shopee marketplace. The population in the research is Heylook Official Shop consumers on the Shopee marketplace the number of which is unknown (infinite). The number of samples in this study was 97 respondents determined using the Lemeshow formula. The sampling technique in this research is non-probability sampling with a purposive sampling method. Data collection was carried out through a questionnaire applied on Google Forms, and measured using a Likert scale. Data analysis uses multiple linear regression with the help of SPSS version 26 software. The findings in this research show that price perceptions and promotions have a significant influence on purchasing decisions, while online customer reviews do not influence Heylook Official Shop Purchase Decisions in the Shopee marketplace. Companies are expected to maintain competitive prices and continue to carry out promotional activities effectively. Companies need to push consumers to provide reviews of the products they purchase so that they become input for other consumers and the company itself.